Mathematical Anxiety Profile of New Mathematics Education Students - Sugiharto; Friantini, Rizki Nurhana; Winata, Rahmat (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
This research is a descriptive qualitative study which aims to describe the mathematical anxiety of new students of the Mathematics Education Study Program at Palangka Raya University both classically and in terms of gender. The subjects of this research were 34 Mathematics Education students at Palangka Raya University, consisting of 21 female students and 13 male students who were selected based on a saturated sampling technique. The technique for collecting data in this research is using a questionnaire. The results of this research can be classically concluded that the majority of new students in the Mathematics Education Study Program at Palangka Raya University have mathematical anxiety. When viewed from gender, the average percentage of mathematical anxiety between female students is greater than that of male students.